Penjaminan Aset Daerah Oleh Pejabat - Mual, Dedi; Tjiptabudi, Jantje; Kuahaty, Sarah Selfina (Pusat Studi Hukum dan Pemerintahan Fakultas Hukum Universitas Pattimura, 2025)
Management of regional assets is the responsibility of regional officials. Law Number 23 of 2014 mandates regional governments to manage assets based on the principle of regional autonomy. In the case of Bupati Kepulauan Meranti, Muhammad Adil, who is suspected of mortgaging regional assets in the form of the regent's office building to a bank, Article 4 of Ministerial Regulation Number 19 of 2016 states that